Effect of necking behavior and of gap size on the cooling rate in hot stamping André - Neto O.* (2016)
In this study, a tailored die quenching experimental method using low closing pressures and an aluminum flat die was developed in order to evaluate the effects of the gap size on the cooling rate in the hot stamping process of a 22MnB5 steel grade. Initially, the necking behavior in hot stamping was investigated by deforming the specimens to different strain levels and subjecting them to quenching in order to assess this effect on the gap profile formed between the die surface and the sample. Next, a controlled gap was promoted in the central region of the aluminum cooler using aluminum spacers (simulating the gap) with different thickness (0.06/0.15/0.40/0.70mm). Then, its effects on the cooling rate and on the hardness after quenching were evaluated. The results showed that the cooling rate is very susceptible to gap size, that the ideal situation occurred when there was no gap, good heat transfer and higher average cooling rates of 120oC/s were achieved, and that when the gap was wider than 0.20mm the average cooling rates were lower than 20oC/s, consequently below the critical 22MnB5 steel cooling for quenching, which is 28oC/s.